Deep-water agglutinated foraminifer from the Fram Strait and Lomonosov Ridge: implications for the opening of the Fram Strait - Kaminski, Michael A.; Silye, Lóránd; Kender, Sev (Anuário do Instituto de Geociências, 2006)
Abstract